Misogyny in public spaces, non-intimate femicides and criminal evidence - Santana García, Viviane Monteiro (2019)
Although the existence of public policies aimed at the prevention of violence aga-inst  women  in  public  spaces  such  as  “Street”,  labor,  or  school/academic  ha-rassment, the invisibility of femicides committed in this same context, known as non-intimate  femicides,  persists.  Despite  the  legal  forecast,  these  are  not  reflec-ted in criminal investigations, sentences and specific prevention policies. The ob-jective of this article is to identify the power relations present in non-intimate fe-micides and their manifestation in criminal evidence, through the analysis of the context of violence against women in public space. From the examination of inter-national documents on the investigation of femicides, misogyny is identified in the evidence through signs of naturalization, internalization, domination and submis-sion of the woman. The exclusion of personal reasons in non-intimate femicide is an evidence of misogyny, expressed in an ambivalent way (mixture of desire and contempt) towards women who transgress their traditional role. It is imperative that non-intimate femicide be made visible so that it can be adequately prevented and sanctioned and guarantee women and girls the right to a life free of violence.